Bedside ultrasound assessment of venous congestion by VExUS protocol in heart failure: clinical associations and prognostic value - Zh. D. Kobalava; R. Sh. Aslanova; A. F. Safarova; M. V. Vatsik-Gorodetskaya (Столичная издательская компания, 2023)
Aim. To evaluate the frequency, dynamics, clinical associations and prognostic value of venous congestion at bedside ultrasound using VExUS protocol in patients with decompensated heart failure (HF).Material and methods. This prospective study included 273 patients over 18 years old with NYHA class II-IV decompensated HF. All patients underwent standard clinical and paraclinical analysis, including NT-proBNP determination, transient elastometry and lung ultrasound. To assess venous congestion by bedside ultrasound using the VExUS protocol, the inferior vena cava (IVC) diameter was estimated and the congestion severity was determined on the deviation of Doppler curves of hepatic, portal and renal veins. If the IVC diameter was ≥2 sm, venous congestion was determined. To assess pulmonary congestion, lung ultrasound (LUS) was performed according to the 8-zone protocol, and the sum of B-lines ≥5 was taken as pulmonary congestion. All patients received standard therapy for heart failure. Statistical analysis was performed in SPSS Statistics program, version 26.0.Results. A high detection rate of venous congestion (75,8%) was revealed in patients with decompensated HF on admission at bedside ultrasound examination according to the VExUS protocol: mild - in 35,5%, moderate - in 12,8%, severe - in 27,5% of patients. The detection rate of venous congestion at discharge was 48,7%: mild - in 28,2%, moderate - in 9,5%, and severe - in 11,0% of cases. Pulmonary congestion on admission was detected in 98,9% of cases. Venous congestion was associated with the severity of HF, NT-proBNP level, renal and cardiac dysfunction, liver stiffness and sum of B-lines. The prognostic role of venous congestion according to the VExUS protocol on re-hospitalization for decompensated HF and the combined endpoint (hospitalization for decompensated HF + allcause death) at 12 months was established.Conclusion. The established incidence, associations, and prognostic value of venous congestion in patients with decompensated HF suggest the utility of bedside ultrasound using the VExUS protocol as an available noninvasive method to optimize therapy and risk stratification.